ANALISIS BIBLIOMETRIK TREN STEM DALAM PEMBELAJARAN BIOLOGI - Astuti, Imelda Puji; Abidin, Zaenal (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
This study investigates research trends, thematic orientations, and developmental patterns of STEM-based biology education integrated with local wisdom in Indonesia from 2021 to 2025. The study is grounded in the growing demand for biology learning that is not only conceptually rigorous but also socially contextualized and responsive to twenty-first-century skill requirements. A quantitative bibliometric approach was employed by analyzing scholarly publications indexed in Google Scholar. Data were processed and visualized using VOSviewer to examine keyword co-occurrence, author collaboration networks, and thematic evolution through network, overlay, and density visualizations. The findings reveal that existing research predominantly focuses on the development of STEM-oriented instructional models aimed at enhancing students’ critical and creative thinking skills. More recent studies indicate an emerging shift toward integrating local wisdom, sustainability issues, and character education within biology learning contexts. This trend reflects a transformation in research orientation from predominantly experimental approaches toward more contextual, learner-centered, and humanistic frameworks. Theoretically, this study contributes to a deeper understanding of the convergence between STEM education, biological sciences, and local cultural values. Practically, the results provide empirical insights to support the development of context-sensitive instructional models and informed educational policies that align with Indonesia’s socio-cultural characteristics. Future research is recommended to examine the effectiveness of locally grounded STEM implementations across different educational levels. ABSTRAKPenelitian ini bertujuan untuk memetakan tren, fokus kajian, dan dinamika perkembangan penelitian pendidikan biologi berbasis STEM yang terintegrasi dengan kearifan lokal di Indonesia selama periode 2021–2025. Kajian ini dilatarbelakangi oleh meningkatnya tuntutan pembelajaran biologi yang tidak hanya menekankan penguasaan konsep sains, tetapi juga relevan dengan konteks sosial-budaya serta mendukung penguatan keterampilan abad ke-21. Penelitian menggunakan pendekatan bibliometrik kuantitatif dengan sumber data berupa artikel ilmiah yang terindeks Google Scholar. Proses analisis dilakukan menggunakan perangkat lunak VOSviewer untuk memvisualisasikan keterkaitan kata kunci, pola kolaborasi penulis, serta evolusi tema penelitian melalui network, overlay, dan density visualization. Hasil analisis menunjukkan bahwa penelitian didominasi oleh pengembangan model pembelajaran STEM yang berorientasi pada peningkatan kemampuan berpikir kritis dan kreatif peserta didik. Selain itu, ditemukan kecenderungan riset mutakhir yang mengarah pada integrasi nilai kearifan lokal, keberlanjutan lingkungan, dan pendidikan karakter dalam pembelajaran biologi. Temuan ini mengindikasikan adanya pergeseran orientasi penelitian dari pendekatan eksperimental semata menuju pembelajaran yang lebih kontekstual dan berpusat pada peserta didik. Secara teoretis, penelitian ini memperkaya kajian tentang integrasi STEM dan kearifan lokal dalam pendidikan biologi, sementara secara praktis dapat menjadi dasar pengambilan kebijakan dan pengembangan model pembelajaran yang kontekstual dan berkelanjutan.